Optimization of Cultural Education Program Using Numerical Techniques - Sahani, Suresh Kumar; Sah, Binod Kumar (Journal of Posthumanism, 2025)
Cultural education is essential for developing socio-cognitive identities and improving intercultural competency in many educational settings. Nevertheless, due to escalating globalization, financial limitations, and diverse regional requirements, it is essential to optimize the framework and implementation of cultural education programs. This research formulates and implements a numerical optimization methodology that combines linear programming with multi-objective decision-making to assess and improve the efficacy of cultural education techniques across various demographic scenarios. The methodology employs official UNESCO cultural education statistics and actual budgetary limitations to ascertain optimum resource distribution and curriculum frameworks. By rigorously using numerical techniques and theoretical research, we demonstrate that mathematical optimization enhances educational efficiency while ensuring fair access and the preservation of cultural variety. Results demonstrate a 27.6% enhancement in program effect efficiency across evaluated areas after improvement. The proposed framework provides educational officials with a comprehensive, data-driven decision-making instrument that integrates cultural pedagogy with mathematical accuracy.